Pendidikan Sosial Berbasis Komunitas dalam Meningkatkan Kesadaran Kewargaan: Systematic Literature Review - Musdalifah; Najamuddin; Ashari (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Community-based social education is a strategic approach for developing civic awareness through participatory, contextual, and collaborative learning experiences. However, research that comprehensively synthesizes the relationship between community-based education and civic awareness remains limited, as previous studies tend to examine social dimensions separately. This study aims to map research developments, implementation forms, contributions, challenges, and opportunities of community-based social education through a Systematic Literature Review approach. The analysis was conducted on 35 scientific articles published during 2021-2026, selected from 120 articles retrieved from Google Scholar, Scopus, ERIC, and ScienceDirect databases using thematic analysis. The findings indicate that this approach strengthens social participation, democratic values, tolerance, solidarity, responsibility, leadership, and the ability to address public issues. Successful implementation is influenced by social capital, multi-stakeholder partnerships, and digital literacy. The novelty of this study lies in developing a conceptual framework that integrates participatory social experiences, social capital, community collaboration, and digital literacy as foundations for strengthening civic awareness sustainably.